Lactobacillus reuteri som probiotisk terapi mot bakteriell vaginit hos avelsråttor - Bergstedt, Johannes (SLU/Dept. of Microbiology, 2004)
Lactobacillus reuteri has been used as probiotics in piglet and chicken feedings as well as in different diary products for humans. In this EEF-work I have shown that L. reuteri can be an alternative for treatment of vaginitis in laboratory rats used for breeding. In a breeding stock with 3000 animals some animals had a vaginal infection with β−haemolytic streptococci group G. The infection was spread among the animals when their heat statuses were checked intra vaginally with an impedance meter. After treatment with L. reuteri both intra vaginally and supplied in the drinking water no animal has been found to carry the infection. I have also shown by in vitro studies that L. reuteri has an inhibitory effect on growth of Streptococcus canis in liquid medium. Furthermore L. reuteri had the ability to adhere to human intestinal cells INT-407 in vitro.